Analysis of renal anomalies in VACTERL association. Issue 10 (5th September 2014) - Cunningham, Bridget K.; Khromykh, Alina; Martinez, Ariel F.; Carney, Tyler; Hadley, Donald W.; Solomon, Benjamin D.
<x xml:space="preserve">Abstract</x> Background VACTERL association refers to a combination of congenital anomalies that can include: vertebral anomalies, anal atresia, cardiac malformations, tracheo‐esophageal fistula with esophageal atresia, renal anomalies (typically structural renal anomalies), and limb anomalies. Methods We conducted a description of a case series to characterize renal findings in a cohort of patients with VACTERL association. Out of the overall cohort, 48 patients (with at least three component features of VACTERL and who had abdominal ultrasound performed) met criteria for analysis. Four other patients were additionally analyzed separately, with the hypothesis that subtle renal system anomalies may occur in patients who would not otherwise meet criteria for VACTERL association. Results Thirty‐three (69%) of the 48 patients had a clinical manifestation affecting the renal system. The most common renal manifestation (RM) was vesicoureteral reflux (VUR) in addition to a structural defect (present in 27%), followed by unilateral renal agenesis (24%), and then dysplastic/multicystic kidneys or duplicated collected system (18% for each). Twenty‐two (88%) of the 25 patients with a structural RM had an associated anorectal malformation. Individuals with either isolated lower anatomic anomalies, or both upper and lower anatomic anomalies were not statistically more likely to have a structural renal defect than those with isolated upper anatomic anomalies (p = 0.22, p = 0.284, respectively). Conclusion Given the high prevalence of isolated VUR in our cohort, we recommend a screening VCUG or other imaging modality be obtained to evaluate for VUR if initial renal ultrasound shows evidence of obstruction or renal scarring, as well as ongoing evaluation of renal health. Birth Defects Research (Part A) 100:801–805, 2014. © 2014 Wiley Periodicals, Inc.